Study of Challenging Calcium Alkoxides in Solution by Electrospray Ionisation Mass Spectrometry (Part 2). Issue 6 (December 2013) - Peruzzo, Valentina; Chiurato, Matteo Andrea; Tomasin, Patrizia; Brianese, Nicola; Traldi, Pietro; Favaro, Monica
Calcium alkoxides in solution give rise to oligomers with different reactivity and solubility and, as observed in a previous investigation, small differences in the ligand structure lead to strong differences in the cluster composition. Electrospray ionisation mass spectrometry (ESI-MS) gives evidence of this behaviour, allowing the identification of these oligomers. In this paper, ESI was applied in the study of calcium alkoxides with different steric hindrances and with additional donor atoms on the ligands. A systematic analysis was conducted by varying the ESI instrumental parameters (voltages, temperatures) to identify the best conditions for the analysis of this class of compounds. Furthermore, particular attention was paid to the study of the best solvent to be employed, considering the possible occurrence of alcoholysis and decomplexation phenomena.